CYTOGENETIC ABNORMALITIES IN PATIENTS WITH PRIMARY AMENORRHEA - Khan, Aysha; Chaudhry, Altaf; Malik, Hamid; Khurshid, Ayesha (Pakistan Armed Forces Medical Journal, 2020)
Objective: To determine pattern of different cytogenetic abnormalities found in patients of primary amenorrhea. Study Design: Cross sectional study. Place and Duration of Study: Chromosomal analysis was carried out on patients who were sent for diagnosis and evaluation of primary amenorrhea to Armed Forces Institute of Pathology, from Mar 2013 to Mar 2017.Methodology: Chromosomal culture and karyotype analysis was done on peripheral blood of 260 patients sent for cytogenetic testing. Sample was collected in sodium Heparin and after 72 hours, 20 metaphases were observed. Results: A total of 260 patients with complaints of primary amenorrhea (PA) were karyotyped. Patients who had karyotype abnormalities were 48 (18.5%). Most common abnormality was Turners syndrome present in 30 individuals (11.5%) including mosaic pattern which was present in 8 patients. Male karyotype was present in 8 (3.07%) patients. Structural chromosomal abnormality Isochromosome (iXq) was seen in 4 patients. One patient had 46X with del Xp (p 1.1). One patient had 46XX t (4; 14). Marker chromosome was seen in one patient. Two patients had 47 XXX.Conclusion: Cytogenetic disorders have a considerable impact on individuals, their families and on society. Early diagnosis of such disorder is imperative. All the cases of primary amenorrhea should have cytogenetic testing.